2022
DOI: 10.3390/ijtm2010010
|View full text |Cite
|
Sign up to set email alerts
|

Thinking Outside the Box: Utilizing Nontraditional Animal Models for COVID-19 Research

Abstract: The ongoing COVID-19 pandemic continues to affect the lives, wellbeing, and stability of communities worldwide. The race to save human lives is critical, and the development of useful translational animal models to elucidate disease pathogenesis and prevention, and to test therapeutic interventions, is essential to this response. However, significant limitations exist with the currently employed animal models that slow our ability to respond to the pandemic. Non-human primates serve as an excellent animal mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 187 publications
(279 reference statements)
0
5
0
Order By: Relevance
“…Through related experimental infection studies, it was found that the Syrian hamsters showed mild to moderate clinical signs after infection, such as weight loss, respiratory distress, lethargy, and hunchback. The animals also exhibited lung lesions similar to those of human COVID‐19, such as macrophage and neutrophil infiltration in the alveoli and bronchi, pulmonary edema, inflammation, and severe alveolar hemorrhage 93 . In addition, SARS‐CoV‐2 replication was mainly observed in the upper and lower respiratory tracts.…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations
“…Through related experimental infection studies, it was found that the Syrian hamsters showed mild to moderate clinical signs after infection, such as weight loss, respiratory distress, lethargy, and hunchback. The animals also exhibited lung lesions similar to those of human COVID‐19, such as macrophage and neutrophil infiltration in the alveoli and bronchi, pulmonary edema, inflammation, and severe alveolar hemorrhage 93 . In addition, SARS‐CoV‐2 replication was mainly observed in the upper and lower respiratory tracts.…”
Section: Discussionmentioning
confidence: 64%
“…The animals also exhibited lung lesions similar to those of human COVID‐19, such as macrophage and neutrophil infiltration in the alveoli and bronchi, pulmonary edema, inflammation, and severe alveolar hemorrhage. 93 In addition, SARS‐CoV‐2 replication was mainly observed in the upper and lower respiratory tracts. Syrian hamsters can mimic the clinical, virological, and histopathological features of human mild to moderate COVID‐19.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Translational animal models are a critical step in delineating immunopathogenesis of disease and developing and testing mitigation strategies and vaccine prototypes prior to human cohort studies, and this is especially crucial under recent circumstances where prior vaccine-or infection-induced immunity does not fully impart cross-protective immunity to newly arising VOCs [9][10][11]. Animal models commonly used for SARS-CoV-2 studies include mice, ferrets, hamsters, mink, non-human primates, cats, and deer [12][13][14][15][16]. However, the utility of these animal models is often limited by one or more factors such as a lack of natural viral-entry receptors (wild-type mice), lack of severe pulmonary disease and acute respiratory distress syndrome (ARDS) (huACE2 transgenic mice, hamsters, ferrets), scarce availability and zoonotic risks (non-human primates), or difficulty in acquiring and handling specific pathogen free (SPF) animals (mink).…”
Section: Introductionmentioning
confidence: 99%